Frequency of sport dreams in Japanese college athletes - Erlacher, Daniel; Fujii, Masato; Tazuke, Shunichi; Sugiyama, Tetsuji; Ganzert, Florian; Schredl, Michael (International journal of dream research, 2020)
In a previous study with German athletes we could show that, the amount of time spent with sport activity in wakefulness is related to the percentage of corresponding dreams about one’s own sport. The present study applied a Japanese translation of the same questionnaire to a Japanese sample of college athletes to explore cultural differences for the frequency of sport dreams. Results showed that Japanese athletes dream about sports as often as German athletes. Furthermore, the duration of sport career, the amount of competitions and the practice hours during wakefulness was related to the frequency of sport dreams, thus supporting the continuity hypothesis of dreaming. The findings indicated that cultural differences are rather small and that other factors like competitions in addition with the emotional involvement might explain better the relationship between waking sport activity and sport dreams.